Photodynamic therapy and cervical intraepithelial neoplasia: current achievements and development prospects - A. I. Ishchenko; I. V. Reshetov; E. A. Sosnova; A. L. Unanyan; A. A. Ishchenko; L. A. Klyukina (Акушерство, гинекология и репродукция)
Nowadays, photodynamic therapy (PDT) is a high-technology actively developing treatment method used in clinical medicine. An interest in this method is primarily due to the fact that its destructive action is based on the mechanisms of free radical oxidation, altered tumor vascular stroma and immune cell-mediated elimination. Owing to current research, improving the quality of photosensitizers and light sources, it becomes possible to expand indications for using this method beyond oncological practice. Generalized data on PDT effectiveness and safety for the treatment of cervical lesions, as well as the ease to use, allow us to attribute this technique to some promising approaches.